Case Report: Robotic ALPPS Procedure for Hepatocellular Carcinoma in the Right Lobe of the Liver - Solomonov, Evgeny; Tzadok, Itamar; Stemmer, Salomon; Biswas, Seema (Frontiers in Surgery, 2021)
Associating liver partition with portal vein ligation for staged hepatectomy (ALPPS) is a surgical procedure for liver malignancy where the volume of the liver remnant is estimated to be too small. We present the first case of two-stage robotic ALPPS procedure, illustrating the steps and advantages of robotic surgery. Materials and Methods: A 68-year-old man with morbid obesity (BMI 40), portal fibrosis, macrovesicular steatosis and poor liver function underwent robotic ALPPS for hepatocellular carcinoma in the right lobe of the liver (segments 5, 7 and 8). A video presentation (https://youtu.be/M50Gumf-4pw) of the operative procedure is accompanied by explanation in the text with embedded corresponding video time points. Results: Both stages of the procedure were performed robotically, with negligible blood loss, and rapid surgical recovery. The patient died 3 years later. Discussion: Robotic ALPPS offers reduced morbidity in major liver surgery for malignancy and may extend survival in meticulously selected patients.